2006
DOI: 10.1074/jbc.m506046200
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptor-α Mediates Gender Differences in Atherosclerosis Induced by HIV Protease Inhibitors

Abstract: As part of highly active antiretroviral therapy, protease inhibitor treatment has significantly increased the lifespan of HIV infected individuals. Many patients, however, develop negative side effects including premature atherosclerosis. We have previously demonstrated that in male low-density lipoprotein receptor (LDL-R) null mice, HIV protease inhibitors induce atherosclerotic lesions and cholesterol accumulation in macrophages in the absence of changes in plasma lipid levels. We determined that these incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 38 publications
0
23
1
Order By: Relevance
“…For example, the nuclear hormone receptor peroxisome proliferator-activated receptor gamma (PPARg) and the cytokines oxidized low-density lipoprotein (oxLDL) and interleukin-4 (IL-4) are known to upregulate CD36 expression. Evidence has shown that HIV protease inhibitors contribute to induce CD36 expression in male mice, but have the opposite effect in female mice (Allred et al, 2006). Hepatic CD36 expression in male and female contrasts with the finding what has Allred made under hormonal and nutritional conditions (Cheung et al, 2007).…”
Section: Introductioncontrasting
confidence: 39%
“…For example, the nuclear hormone receptor peroxisome proliferator-activated receptor gamma (PPARg) and the cytokines oxidized low-density lipoprotein (oxLDL) and interleukin-4 (IL-4) are known to upregulate CD36 expression. Evidence has shown that HIV protease inhibitors contribute to induce CD36 expression in male mice, but have the opposite effect in female mice (Allred et al, 2006). Hepatic CD36 expression in male and female contrasts with the finding what has Allred made under hormonal and nutritional conditions (Cheung et al, 2007).…”
Section: Introductioncontrasting
confidence: 39%
“…A study in LDL-null mice examined the effects of ritonavir and amprenavir on cholesterol accumulation in macrophages, showing that females had lowers levels than males. The protective effect was lost after genetically removing estrogen receptor-alpha 28 .…”
Section: Eira Et Al Aids Treatment and Arterial Stiffnessmentioning
confidence: 91%
“…Depending on the experimental system used, the mechanisms of CD36 over-expression by ritonavir involves protein kinase C (PKC) (Bradshaw et al, 2006;Dressman et al, 2003), the estrogen receptor alpha (ERa) (Allred et al, 2006), as well as cellular proteasome inhibition in human THP-1 monocytes (Munteanu et al, 2004a(Munteanu et al, , 2005. In ritonavir-treated mouse macrophages, PKC activation and increased PPARc and CD36 expression are reverted by the nucleoside reverse transcriptase inhibitor didanosine via increased ubiquitination and degradation of PKCa, whereas a-tocopherol is without effect in this in vivo model (Bradshaw et al, 2006;Dressman et al, 2003).…”
Section: Over-expression Of Scavenger Receptor Cd36 By Ritonavir Is Pmentioning
confidence: 99%